Adapting an evidence-based intervention targeting HIV-infected prisoners in Malaysia - Copenhaver, M.M.; Tunku, N.; Ezeabogu, I.; Potrepka, J.; Zahari, M.M.A.; Kamarulzaman, A.; Altice, F.L. (2011)
HIV-infected prisoners in Malaysia represent a critical target population for secondary HIV risk reduction interventions and care. We report on the process and outcome of our formative research aimed at systematically selecting and adapting an EBI designed to reduce secondary HIV risk and improve adherence to antiretroviral therapy among soon-to-be-released HIV-infected prisoners. Our formative work involved a critical examination of established EBIs and associated published reports complemented by data elicited through structured interviews and focus groups with key stakeholders, members of the target population, and their family members. Based on all information, we adapted the Holistic Health Recovery Program targeting people living with HIV (HHRP+), an EBI, to consist of eight 2-hour sessions that cover a range of specified topics so that participants may individually apply intervention content as needed to accommodate their particular substance abuse, HIV risk, and antiretroviral adherence issues. This study provides a complete example of the process of selecting and adapting an EBIâtaking into account both empirical evidence and input from target organization stakeholders and target population members and their familiesâfor use in real world prison settings where high-risk populations are concentrated.